System Relevance and Firm Performance Due to COVID-19 - Michael Johannes Böhm; Pamela Qendrai (Institute of Labor Economics (IZA), 2023)
We study the impact of COVID-19 on firm performance. Using financial accounts of a large number of German firms, we document that industry affiliation is an important economic dimension of the crisis. Motivated by this fact, we analyze an important industry-specific regulation, system relevance, which allows businesses to remain open in times of lockdown and other restrictions. A difference-in-differences estimation strategy shows that relative revenues of system-relevant firms increase by 6-9 percent and profits by 17-25 percent due to COVID. Controlling for channels that are arguably not driven by the system-relevance regulation, the impact on revenues decreases but remains significant. Overall, results indicate that regulations affecting the ability to operate as well as industry-level shocks play important roles for firm performance during a pandemic-induced crisis.
Keywords: H12; L25; 330; system relevance; industry shocks; firm performance; COVID-19